EFEKTIVITAS SENAM KAKI DAN RENDAM AIR HANGAT TERHADAP SIRKULASI DARAH PERIFER PADA PASIEN LANSIA DIABETES MELLITUS - Maryani, Dwi Maryani; -, Handoyo; Rosyadi, Imron Rosyadi; Poltekkes Kemenkes Semarang, Prodi Keperawatan Purwokerto,; UNSOED, Jurusan Keperawatan; RSUD Banyumas, Perawat pelaksana RSUD Banyumas (LPPM STIKES MUHAMMADIYAH GOMBONG, 2013)
Diabetes mellitus is characterized by blood glucose levels exceed the normal and metabolic disorders of carbohydrates, fats and proteins caused by insulin deficiency. Complications that can occur is long term vascular complications, they are microangiopathic and macroangiopathic. Microangiopathic complications in the form of blood circulation disorders in lower extremities or legs. Foot exercise and immersion warm water are therapy for improve blood circulation in the legs. The aim of this study isÂ to know the effectiveness between foot exercise and immersion warm water to peripheral blood circulation in DM eldery patients in working area of (Community Health Center South Purwokerto And East Purwokerto). This study was quasy experiment with two group pre test and post test design without control. Sampling method was total sampling. Samples numbered 38 people. The statistical analysis in this study used paired t-test and independent t test. Based on independent t test analysis show that p value were at 0.039 which is smaller than Î± (5%) or 0,05. Thus Ho was rejected and Ha accepted. It can be summarized that there were differences in the effectiveness between foot exercise and immersion warm water to peripheral blood circulation in DM elderly patients in working area of Community Health Center South Purwokerto And East Purwokerto. There were differences in the effectiveness between foot gymnastyc and immersion warm water to peripheral blood circulation in DM elderly patients in working area of Community Health Center South Purwokerto And East Purwokerto. Keywords : Foot gymnastic, immersion warm water, peripheral blood circulation, Diabetes Mellitus.